Соціально-економічні наслідки польської аграрної політики в Галичині у міжвоєнний період - Виздрик, В. С. (Видавництво Львівської політехніки, 2014)
Зроблено спробу розглянути наслідки впровадження польським урядом аграрної реформи, яка передбачала планомірну польську сільськогосподарську колонізацію українських земель за допомогою військового та цивільного осадництва. Аграрна політика не зупинила процесу здрібнення та зубожіння селянських господарств, а загострила соціальні та національні суперечності між українським та польським населенням краю. This article considers the results of the introduction agrarian reforms by the Polish government which included systematic agricultural colonization of the Ukrainian lands by Polish with the help of military and civilian colonization. The agricultural policy has not stopped the process of pauperization of the peasant farms exacerbated social and national contradictions between the Ukrainian and Polish people of the region. Eastern Galicia and a western part of Volyn of the interwar period of the last century became the center of socioeconomic and socio-political inter-ethnic conflict between the Ukrainian and Polish people of the region. The government of Poland tried to give “Eastern lands” the Polish character and it held systematic agricultural policy in the eastern and south-eastern provinces which included the development of Ukrainian lands with the help of military and civilian colonists. They have become the social support of the economic policy of the government in the eastern border of Poland. It should be mention that agricultural reform which was led by the Polish government, starting from the legal normative base and completing its realization, was anti-Ukrainian. The consequence of socio-economic policy of the state the aggravation of the land problem and discontent of the Ukrainian peasants that was one of the main reason of peasant protests and development of the Ukrainian national liberation movement.
Keywords: польський уряд; аграрна реформа; селянські господарства; Polish government; agrarian reforms; Ukrainian peasants